Healthcare Expenditures Associated With Comorbid Anxiety and Depression Among Adults With Migraine - Alwhaibi, Monira; Meraya, Abdulkarim M.; AlRuthia, Yazed (Frontiers in Neurology, 2021)
Introduction: Depression and anxiety are common among patients with migraine and usually associated with a humanistic and financial burden. This study aims to examine the direct healthcare expenditures among adults with migraine alone or with comorbid anxiety and/or depression. Methods: This was a retrospective cross-sectional study using 2012, 2014, and 2016 Medical Expenditure Panel Survey data. Adult patients aged ≥22 years with migraine headache were included in the study. The direct healthcare expenditures of four migraine groups (migraine alone, migraine and anxiety, migraine and depression, and migraine and both conditions) were compared. Results: There were 1,556 patients who met the inclusion criteria and eventually enrolled in the study. Approximately 42% of the study sample had migraine with comorbid depression and/or anxiety (16.1% have depression, 12.3% have anxiety disorder, and 13.9% have both). The mean total healthcare expenditures of adults with migraine alone (6,461) were significantly lower than those with comorbid depression and anxiety (11,102), comorbid anxiety (10,817), and comorbid depression (14,577). Migraine with comorbid anxiety and depression was significantly associated with incremental costs of 1,027 in outpatient and 662 emergency room healthcare expenditures and prescription drug compared to the migraine alone group. Conclusions: The healthcare expenditures associated with migraine with comorbid depression and/or anxiety are significantly higher than those without mental health comorbidities. Therefore, regular depression and anxiety screening for patients with migraine may help reduce the healthcare expenditures associated with depression and/or anxiety comorbidities and improve the quality of care.